TEKNIK DAN METODE PENERJEMAHAN KALIMAT TANYA PADA SUBTITLE SERIAL TV SHALAHUDDIN ALAYYUBI VERSI MNCTV - Ahmad Fauzan Shidiq, Abdul Malik (CMES (Center of Middle Eastern Studies), 2015)
The article discusses about techniques and methods of translation used to ranslate the interrogative sentence of Shalahuddin Al Ayyubi‟s Subtitle in MNCTV's version. The purposes of the research in this article are: (1) To describe the techniques of translating interrogative sentences used in making Shalahuddin Al Ayyubi‟s subtitle. (2) To describe the translation methods used in making subtitle of Salahuddin Al Ayyubi's film. The method used in the research is descriptive qualitative one. The data source is question sentences on subtitle‟s film of Salahuddin Al Ayyubi in MNCTV version on 1 episodes. In the first formulation, data were collected using random sampling techniques in the form of interrogative sentence then determining the type of translation techniques used. After that, making the percentage of translation techniques to know about the one that are most widely used. The second problem is analyzed based on the problem analysis results at the first formulation. Translation method is determined based on the percentage of translation techniques used. Both of problems are analyzed with descriptive qualitative method. Based on the results of the study it can be concluded that there are 12 translation techniques used. The most widely used technique is the technique of reduction (24.4%). While the least used technique is the technique of adaptation, compensation and discursive creation (2.2%). As for the method of translation used is the target language emphasis method with percentage of the translation techniques that oriented on target language (71,1%) compared to ones that oriented on source language (28,9%).